Formulasi dan Evaluasi Sediaan Body Scrub Kombinasi Ekstrak Daun Salam (Syzygium polyanthum (Wight.) Walp. dan Beras Putih (Oryza sativa L. ) Sebagai Antioksidan - Riza Dwiningrum; Mida Pratiwi; Vicko Suswidiantoro; Clarissa Helmavicha Amanda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Body scrub is a cosmetic that acts as an exfoliator, which has the ability to remove dead skin cells and provide protection to the skin from free radical attacks. One of the natural ingredients that can be used as raw material for body scrub is bay leaf (Syzygium polyanthum (Wight.) Walp) and white rice (Oryza sativa L.) with flavonoids, tocopherols, and tocotrienols that act as natural antioxidants. The study purpose was: This study aims to determine the physical quality characteristics and antioxidant activity of bay leaf and white rice extract body scrub preparations using UV-Vis spectrophotometry. Materials and methods. The method used in the study was experimental in the laboratory by making three formulations of body scrub concentrations FI (3%,10%), FII (6%,10%), and FIII (9%,10%). Results: The results of the study stated that the three formulas met the requirements of the physical quality test, but did not meet the protective power test and the preparations had different antioxidant values, where the best formula that had a very strong antioxidant activity value was in formula III with an IC50 value obtained of 45.452, which was included in the very strong category. Conclusions. The research conducted is expected to be an initial reference for further researchers to conduct pharmacological activity tests such as antibacterial or anti-inflammatory in vivo to support the further benefits of the preparations made.